Complexity in managing the blood transfusion process: experience of an Italian Academic Hospital. (13th November 2019) - Poletto, M; Scarpis, E; Bianchet, B; Ruscio, E; Degan, S; Farneti, F; De Angelis, V; Brusaferro, S
Abstract: Issue: Blood components transfusion is a high-risk process due to its complexity and possible consequences in case of error. Preventing mistakes and acting promptly if they occur is a duty of healthcare organizations. The Italian Ministry of Health has drafted a specific recommendation with the aim of reducing transfusion errors. Description of the problem: Following a transfusion error occurred in July 2018, a multidisciplinary group including professionals from Clinical Risk Unit (CRU) and Transfusion Department of the Academic Hospital of Udine, carried out an analysis of the blood components issuing process. The 20 most critical steps were identified and grouped into 3 areas: 1)single samples processed individually, 2)appropriate application compliance, 3)environmental interferences. For each step shared solutions were identified and then implemented as new standard practices. From February to March 2019, CRU randomly observed 23 blood components assignments using tracer methodology, evaluating staff's compliance with the new recommended practices (NRP). Results: For the sample processing (area 1, n.10 practices), adherence to all ten NRP was 100% (26/26). For the appropriate application compliance (area 2, n.8 practices), adherence to 7 NRP was 100% (11/11), whereas for one (punctual registration of non-conformities) adherence was 86% (6/7). For the environmental interferences (area 3, n.2 practices), adherence to one practice was 100% (2/2), whereas for the other one (avoid answering to incoming phone calls) adherence was 75% (3/4). Overall, professionals behaviour was consistent with the NRP in the observed period. Lessons: Identification of critical issues by a multidisciplinary team and measuring the adherence to new practices is crucial in managing the complexity of blood transfusion process. Tracer methodology, used by CRU to verify adherence to new standard, also allows the hospital to monitor the progress of the achieved performances over time. Key messages: Multidisciplinary analysis of the blood transfusion process and shared development of new standard by all professionals favours their compliance in the practice. Tracer methodology is a useful tool to evaluate adherence to recommended practices and monitor the complexity of transfusion process over time.